2018
DOI: 10.1111/bjh.15248
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐reported outcomes of multiple myeloma patients treated with panobinostat after ≥2 lines of therapy based on the international phase 3, randomized, double‐blind, placebo‐controlled PANORAMA‐1 trial

Abstract: The phase 3 PANORAMA-1 trial led to regulatory approvals of panobinostat (PAN) in combination with bortezomib (BTZ) and dexamethasone (DEX) for the treatment of multiple myeloma after ≥2 prior regimens, including BTZ and an immunomodulatory drug. Patient-reported outcomes (PROs) were assessed in PANORAMA-1, with data available for 73 patients in the PAN + BTZ + DEX arm and 74 patients in the placebo (PBO) + BTZ + DEX arm. Per the European Organisation for Research and Treatment of Cancer Quality of Life Questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…In agreement with previous studies on treatment preferences in patients with MM [3,10], participants prioritized increased life expectancy as a treatment benefit of utmost importance. As in previous studies, patients reported high symptom burden, including symptoms associated with HRQoL [1,2,4,5,7,9]. In agreement with another qualitative study on treatment preferences in MM [3], symptoms such as fatigue and bone pain, and side effects such as gastrointestinal symptoms and peripheral neuropathy, were the most frequently discussed by patients as significantly disruptive to HRQoL.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In agreement with previous studies on treatment preferences in patients with MM [3,10], participants prioritized increased life expectancy as a treatment benefit of utmost importance. As in previous studies, patients reported high symptom burden, including symptoms associated with HRQoL [1,2,4,5,7,9]. In agreement with another qualitative study on treatment preferences in MM [3], symptoms such as fatigue and bone pain, and side effects such as gastrointestinal symptoms and peripheral neuropathy, were the most frequently discussed by patients as significantly disruptive to HRQoL.…”
Section: Discussionsupporting
confidence: 87%
“…Multiple myeloma (MM) is the second most common hematological cancer and is characterized by high levels of mortality [1][2][3][4]. Despite recent treatment advances, MM remains incurable [1][2][3][5][6][7][8] and becomes harder to treat over time [2,3,8]. Development of new treatment options, particularly those that can be tolerated over the long term, is an ongoing priority.…”
Section: Introductionmentioning
confidence: 99%
“…The OS benefit in the subgroup of patients with ≥ 2 prior treatments was 5 months. In the PANORAMA-1 study, HRQoL scores after 48 weeks of treatment with bortezomib/dexamethasone, with or without panobinostat, showed no benefit, and no significant difference in OS was observed between treatments [43]. Interestingly, it has been reported that there may be a relationship between improvement in HRQoL and treatment response in patients with cancer [36,44].…”
Section: Discussionmentioning
confidence: 98%
“…Despite recent treatment advances, multiple myeloma (MM) remains an incurable disease with a substantial negative impact on patients' health-related quality of life (HRQoL). [1][2][3][4][5][6][7][8][9] MM treatment is associated with demanding administration and monitoring schedules 2 as well as adverse events. 1,2,5 Since treatment until disease progression (rather than a fixed-duration regimen) is recommended, 6,10 and because treatment with novel agents has extended progression-free survival (PFS), 11 assessment of the impact of treatment on patients' long-term HRQoL is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5 Since treatment until disease progression (rather than a fixed-duration regimen) is recommended, 6,10 and because treatment with novel agents has extended progression-free survival (PFS), 11 assessment of the impact of treatment on patients' long-term HRQoL is warranted. 3,7,9,12,13 Moreover, MM is primarily a disease of older persons 1 for whom treatment selection may be complicated by co-morbidities, such as diabetes or cardiovascular disease. 14 Patient-reported outcomes (PROs), including evaluation of the impact of treatment on HRQoL, offer valuable insights to supplement clinical endpoints and aid in therapeutic decision-making.…”
Section: Introductionmentioning
confidence: 99%